2019
DOI: 10.1093/sysbio/syz064
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic Systematics and Evolution of the Spider Infraorder Mygalomorphae Using Genomic Scale Data

Abstract: The infraorder Mygalomorphae is one of the three main lineages of spiders comprising over 3000 nominal species. This ancient group has a worldwide distribution that includes among its ranks large and charismatic taxa such as tarantulas, trapdoor spiders, and highly venomous funnel-web spiders. Based on past molecular studies using Sanger-sequencing approaches, numerous mygalomorph families (e.g., Hexathelidae, Ctenizidae, Cyrtaucheniidae, Dipluridae, and Nemesiidae) have been identified as non-monophyletic. Ho… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
100
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 100 publications
(106 citation statements)
references
References 143 publications
(216 reference statements)
3
100
2
1
Order By: Relevance
“…This study revealed a suite of morphological characters (Appendix ), from both male and female spiders, which will be valuable in future taxonomic revisions within the tribe, and which should be considered during taxonomic or phylogenetic studies on other mygalomorph groups too, especially idiopids and their closest relatives within the Domiothelina (i.e. Ctenizidae, Euctenizidae, Migidae and Halonoproctidae; Opatova et al, 2020). The challenging morphology of mygalomorph spiders has frequently been lamented by arachnologists; shared plesiomorphic characters and frequent homoplasy in derived characters obfuscate phylogenetic signal (Raven, 1985; Goloboff, 1993; Bond, 2012; Opatova et al, 2020), whereas at lower phylogenetic levels, discrete morphological differences may not be present between taxa that display interspecific levels of genetic divergence (see, e.g., Satler et al, 2013; Leavitt et al, 2015; Montes de Oca et al, 2016).…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations
“…This study revealed a suite of morphological characters (Appendix ), from both male and female spiders, which will be valuable in future taxonomic revisions within the tribe, and which should be considered during taxonomic or phylogenetic studies on other mygalomorph groups too, especially idiopids and their closest relatives within the Domiothelina (i.e. Ctenizidae, Euctenizidae, Migidae and Halonoproctidae; Opatova et al, 2020). The challenging morphology of mygalomorph spiders has frequently been lamented by arachnologists; shared plesiomorphic characters and frequent homoplasy in derived characters obfuscate phylogenetic signal (Raven, 1985; Goloboff, 1993; Bond, 2012; Opatova et al, 2020), whereas at lower phylogenetic levels, discrete morphological differences may not be present between taxa that display interspecific levels of genetic divergence (see, e.g., Satler et al, 2013; Leavitt et al, 2015; Montes de Oca et al, 2016).…”
Section: Discussionmentioning
confidence: 92%
“…Ctenizidae, Euctenizidae, Migidae and Halonoproctidae; Opatova et al, 2020). The challenging morphology of mygalomorph spiders has frequently been lamented by arachnologists; shared plesiomorphic characters and frequent homoplasy in derived characters obfuscate phylogenetic signal (Raven, 1985; Goloboff, 1993; Bond, 2012; Opatova et al, 2020), whereas at lower phylogenetic levels, discrete morphological differences may not be present between taxa that display interspecific levels of genetic divergence (see, e.g., Satler et al, 2013; Leavitt et al, 2015; Montes de Oca et al, 2016). Selection has been suggested as the potential cause of these issues; adaptation to the sedentary, fossorial lifestyle shared by most mygalomorph taxa may select against significant departures from the morphological “norm” which clearly fits their ecological niche (Bond and Hedin, 2006; Ortiz et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Trapdoor spiders belong to an ancient lineage of chelicerate arthropods, the spider infraorder Mygalomorphae, which includes charismatic fauna such as tarantulas and Australian funnel web spiders [1]. These spiders are sedentary, fossorial predators that build silk-lined burrows; females are non-vagile and mature males emerge seasonally to search for females.…”
Section: Introductionmentioning
confidence: 99%